The Effect of Leadership Styles on the Business Performance of SMEs in Malaysia - Aziz, Roslan Abdul; Abdullah, Mohd Hussin; Tajudin, Anas (International Journal of Economics, Business and Management Studies, 2013)
This paper investigates the effect of leadership styles on the business performance of SMEs in Malaysia. The owner/managers were sent a package of questionnaires which comprised the Multifactor Leadership Questionnaire MLQ 5X, the Business Performance BP questionnaire and the demographic questionnaire. The findings revealed that there were significant positive relationships between transactional leadership and business performance and transformational leadership and business performance. The findings also found that passive-avoidant leadership was negatively correlated with business performance. The findings can be generalized that transactional and transformational leadership styles were the dominant form of leaderships displayed by the owner/managers of the SMEs in Malaysia. This study also provides an opportunity to expand the research on other industries such as manufacturing, constructions, agricultures and telecommunications.